Two-Colour Topology Finding of Quad-Mesh Patterns. (August 2021) - Oval, R.; Mesnil, R.; Van Mele, T.; Block, P.; Baverel, O.
Abstract: The patterns of many structural systems must fulfil a property of two-colourability to partition their elements into two groups. Such examples include top versus bottom layers of continuous beams in elastic gridshells, corrugated versus non-corrugated directions in corrugated shells or warp versus weft threads in woven structures. Complying with such constraints does not depend on the geometry but on the topology of the structure, and, more specifically, on its singularities. This paper presents a search strategy to obtain patterns that fulfil this topological requirement, which represent only a fraction of the general design space. Based on an algebra for the exploration of the topology of quad meshes, including a grammar and a distance, a topology-finding algorithm is proposed to find the closest two-colour quad-mesh patterns from an input quad-mesh pattern. This approach is expressed as the projection to the two-colourable subspace of the design space. The distance underlying the definition of the projection measures the similarity between designs as the minimum number of topological grammar rules to apply to modify one design into another. A design application illustrates how two-colour topology finding can complement workflows for the exploration of structural patterns with singularities informed by the system's topological requirements. Highlights: Topological property of two-colourability of quad-mesh patterns Topological requirements on singularities and density of quad-mesh patterns Different characterisations of the singularity requirement A grammar-based distance to evaluate the topological similarity of quad meshes A projection to make a quad mesh two-colourable A search algorithm for two-colour topology finding Several examples illustrating the application of these concepts